Answer: False
===================================================
Step-by-step explanation:
Recall that the FOIL rule says
![(a+b)^2 = (a+b)(a+b) = a^2+2ab+b^2](https://img.qammunity.org/2022/formulas/mathematics/high-school/9qd2d1nqatm7rtaool342rblgbdd0f8ahb.png)
If we plug in
and
, then you should find that
![(a+b)^2 = a^2+2ab+b^2\\\\(√(2)+√(3))^2 = (√(2))^2+2*√(2)*√(3)+(√(3))^2\\\\(√(2)+√(3))^2 = 2+2*√(2*3)+3\\\\(√(2)+√(3))^2 = 5+2√(6)\\\\](https://img.qammunity.org/2022/formulas/mathematics/high-school/l52fmd2kfp9hnhioalpnh1950gd74i61pn.png)
So that 5 the student got is close, but there's a missing term needed to be added on: namely the
term.